The tourist activity of fitness trainers and participants of groups based on Lodz fitness clubs - Grzelak, Julia (Turystyka w badaniach podstawowych, 2023)
This article was developed on the basis of a bachelor’s thesis. The presented results, provided by using surveys, concern the tourist activity of trainers and participants of groups during long-term (summer and winter holidays) and short-term (weekend and festive) trips in 2019–2020. The most extensive results concern the first of them, as it takes into account motive, time and length, activities undertaken, destinations, means of transport, the method of organization and with whom the trip was taken. Festive and weekend trips were treated more generally and only the time and place were checked. In the case of all trips, reasons for not taking them were also asked. In addition, the article presents an overview of clubs in Lodz and a short description of trainers and participants in group fitness classes.